Thermal properties of monosubstituted ferrocene derivatives: A series of new ferrocenomesogens - Loubser, C; Imrie, C (Perkin transactions. 2, 1997)
The preparation of a series of 1-substituted ferrocene derivatives is described. The structure of the substituent was varied systematically in order to determine the structural limits within which mesogenic behaviour is retained. The compounds are particularly useful for stabilizing the nematic phase, the range of which was increased substantially by extending the aromatic core of the substituent. Selective lateral fluorination was successfully used to lower the nematic temperatures as well as to suppress any smectic phases. Derivatives with no more than two rings in the core only display the crystal smectic B phase. The significance of substituents on the cyclopentadienyl rings is discussed with reference to their electronic properties and their effect on the stability of the compounds.